2015
DOI: 10.1051/0004-6361/201322689
|View full text |Cite
|
Sign up to set email alerts
|

The matter distribution inz~ 0.5 redshift clusters of galaxies

Abstract: We present an optical analysis of a sample of 11 clusters built from the EXCPRES sample of X-ray selected clusters at intermediate redshift (z ∼ 0.5). With a careful selection of the background galaxies, we provide the mass maps reconstructed from the weak lensing by the clusters. We compare them with the light distribution traced by the early-type galaxies selected along the red sequence for each cluster. The strong correlations between dark matter and galaxy distributions are confirmed, although some discrep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 120 publications
7
16
1
Order By: Relevance
“…A correlation between the two has been observed in several studies (e.g. Lambas et al 1988;Panko et al 2009;Niederste-Ostholt et al 2010;Soucail et al 2015) and can be interpreted as either a collimated infall of galaxies from filaments (e.g. Dubinski 1998) or due to tidal interactions (e.g.…”
Section: Optical Morphologymentioning
confidence: 73%
“…A correlation between the two has been observed in several studies (e.g. Lambas et al 1988;Panko et al 2009;Niederste-Ostholt et al 2010;Soucail et al 2015) and can be interpreted as either a collimated infall of galaxies from filaments (e.g. Dubinski 1998) or due to tidal interactions (e.g.…”
Section: Optical Morphologymentioning
confidence: 73%
“…While structures 5 and 6 might have an optical counterparts, structure 4 and 7 very likely correspond to fake peaks or to a small group at a different redshift for structure 4. Structures 4 and 6 are also detected in Soucail et al (2015). A larger structure is found at the southwest (8 at 5.5σ κ ), which is not at the cluster redshift, given that it is not detected through the galaxy density contours, but could also be due to a contamination from stars in its vicinity.…”
Section: Individual Clustersmentioning
confidence: 89%
“…It is highly substructured as already found in Guennou et al (2014) and confirmed here by the presence of three spatially separated components: dark matter, X-ray gas, and galaxies. No substructures are detected in the mass reconstruction of Soucail et al (2015), but they used a smoothing kernel more than twice as large as ours. The most important substructures are those noted 2 and 3, the first to the south with a 5σ κ significance and the second to the northeast with a 4.3σ κ significance.…”
Section: Macsj0454mentioning
confidence: 90%
See 1 more Smart Citation
“…The deflection of light leads to one important theoretical and observational tool in modern astronomy and cosmology: the gravitational lensing (GL). After the observation of the first GL in 1979 [5], many features, including luminous arcs [6,7], Einstein cross [8], Einstein rings [9], GL of CMB [10][11][12], and supernovas [13,14] and even composition features such as the SN Refsdal which combines the Einstein cross with the GL of supernova [15] have been observed. The GL were then used to study properties of the lens [16], coevolution of supermassive black holes (BHs) and galaxies [17], cosmological parameters such as large scale structure (for a review see [18]), properties of the supernova [19], dark matter substructure [20,21], and to discriminate alternative gravitational theories.…”
Section: Introductionmentioning
confidence: 99%